The Effectiveness of The Kangaroo Method Care (KMC) On Body Temperature Stability In Low Birth Weight (LBW) Babies - Lestari Makmuriana; Dewi Ultari Srimentari; Tri Wahyuni; Lilis Lestari (Syntax Literate, 2022)
Low birth weight is a baby born with birth weight of less than 2500 grams. Babies with low birth weight have a great potential to experience various health problems as a result of incomplete and mature organs and body functions. One of the problems than often occurs is the imperfect regulation of body temperature. To maintain the stability of body temperature, a methoded is used, namely the Kangaroo Method Care (KMC). The purpose of this study was to determine the effectiveness of the Kangaroo Method Care (KMC) on the stability of body temperature in Low Birth Weight (LBW) infants in the Perinatology Room of The Regional Public Hospital dr Achmad Diponegoro Putussibau. This research is a quantitative research. This study uses a quasy-experimental without a control group with the design used is a pretest post test one group design. This research test using Paired T-Test. This research was conducted in the Perinatology Room of the Regional Public Hospital dr Achmad Diponegoro Putussibau which was carried out on April 12th – June 24th 2021 with a total of 25 LBW respondents. The results of statistical tests based on the t-test, the count value was -11,126 with a p-value 0f 0,000. It is known that the p-value is 0,000 < α (0,05), this indicates that there is an effect of the Kangaroo Method Care (KMC) on the stability of body temperature in Low Birth Weight (LBW) infants in the Perinatology Room of The Regional Public Hospital dr Achmad Diponegoro Putussibau